2021
DOI: 10.1001/jamahealthforum.2021.2001
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Address Food Insecurity Among Adults in Canada and the US

Abstract: IMPORTANCE Inadequate access to food is a risk factor for poor health and the effectiveness of federal programs targeting food insecurity, such as the Supplemental Nutrition Assistance Program (SNAP), are well-documented. The associations between other types of interventions to provide adequate food access and food insecurity status, health outcomes, and health care utilization, however, are unclear.OBJECTIVE To review evidence on the association between food insecurity interventions and food insecurity status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 55 publications
2
37
0
Order By: Relevance
“…HRSNs that have been the subject of considerable interest and investment, such as food and housing insecurity, 34,35 were not uniformly associated with increases in acute care utilization.…”
Section: All-cause Ed Visitsmentioning
confidence: 96%
“…HRSNs that have been the subject of considerable interest and investment, such as food and housing insecurity, 34,35 were not uniformly associated with increases in acute care utilization.…”
Section: All-cause Ed Visitsmentioning
confidence: 96%
“…We found no significant effects from the F&V voucher on food security status and F&V intake in pregnant WIC recipients with low income. This stands in contrast to a growing body of evidence for these programs, including a 2021 systematic review and meta-analysis of 39 randomized and observational studies—providing food or resources for food—that reported statistically significant reductions in food insecurity [ 25 ], as well as a 2022 pooled analysis of 17 food pharmacy or food prescription programs which showed a significant mean increase in daily servings of F&Vs (mean = 0.77; 95% CI: 0.30 to 1.24) [ 26 ]. Perhaps most relevant to our study’s focus; the early analysis of the COVID-19-related WIC CVB augmentation demonstrates significant changes to children’s total daily F&V consumption, increasing by 1/3 cup from 2.01 cups before the CVB increase to 2.31 cups [ 27 ].…”
Section: Discussionmentioning
confidence: 79%
“…Identifying patterns of modifiable factors may serve as key targets for prevention efforts and can inform the development of programs that target multiple modifiable, co-occurring risk factors. For example, we included unemployment, depression, and food insecurity, all of which co-occur and benefit from secondary or targeted intervention ( De Marchis et al, 2019 ; Oronce et al, 2021 ; Paul & Moser, 2009 ). Alternatively, we define non-modifiable factors (e.g., sex) as stable factors that are less likely to be altered through prevention programming, yet are associated with health outcomes.…”
Section: Overviewmentioning
confidence: 99%